The Management of Changes in the Madarijul Ulum Islamic Boarding School Bandar Lampung in Producing Ulama Ul Amilin Imamul Muttaqin - Ahmad Mutho’i; Ahmad Fauzan; Junaidah (CV. Creative Tugu Pena, 2025)
Change management at Pondok Pesantren Madarijul Ulum in Bandar Lampung serves as a crucial strategy in shaping Islamic scholars who are not only well-versed in Islamic sciences but also equipped with adaptive leadership skills responsive to contemporary challenges. This study aims to analyze the change process, encompassing the identification of needs, planning, implementation, resistance, and evaluation within the pesantren's educational management system. Employing a qualitative approach, data were collected through observation, in-depth interviews, and documentation to gain a comprehensive understanding of the dynamics of change taking place. The findings reveal that curriculum innovation, capacity building of educators, and the development of a structured student leadership pipeline are central focuses of the transformation process. Despite encountering resistance from individuals adhering to traditionalist approaches, the use of persuasive communication and participatory methods proved effective in mitigating conflict and enhancing the involvement of all pesantren stakeholders. Periodic evaluations have also played a significant role in aligning implemented changes with the institution’s overarching vision. These findings contribute to the existing literature on change management in faith-based educational institutions and offer practical recommendations for strengthening teacher training, increasing stakeholder participation, and fostering institutional collaboration. Consequently, pesantren can evolve into centers of excellence that produce knowledgeable, ethical, and globally responsive Muslim leaders.